EVALUASI PELAKSANAAN SISTEM AKUNTANSI BELANJA PADA DINAS SOSIAL TENAGA KERJA DAN TRANSMIGRASI KABUPATEN MINAHASA SELATAN SESUAI PP NO 71 TAHUN 2010 - Lasut, Marsella; Morasa, Jenny; Mawikere, Lidia M. (Universitas Sam Ratulangi, 2017)
Government Regulation No. 71 Year 2010 about government accounting standards, shopping is is recognized when an expense is made from the State / Region general account. Shopping accounting is structured to meet accountability requirements in accordance with the provisions. This study aims to Evaluate the Implementation ofÂ Shopping Accounting System at office of Social, Manpower, and Transmigration of District South Minahasa Province in accordance with Regulation No.71 Year 2010.Â The object of office of Social, Manpower, and Transmigration of District South Minahasa. The method used in this research is qualitative descriptive analytical method. The result of the Social Service Research of Manpower and Transmigration is always guided by the existing regulations and in the Implementation of Shopping Accounting System, has applied or has been in accordance with Government Regulation No. 71 of 2010 on Government Accounting Standards.Keywords : Implementation, System, Accounting, Shopping